Rancangan dan Implementasi Sekolah Lapang Pengelolaan Tanaman Terpadu Padi - Rangga Ditya Yofa; Mewa Ariani; I Ketut Kariyasa; Achmad Suryana (Analisis Kebijakan Pertanian, 2016)
Field School-Integrated Crop Management (FS-ICM) was one of components within the National Rice Production Enhancement Program implemented by the Ministry of Agriculture in the period of 2009−2014. With the support of a large amount of budget, FS-ICM implementation was expected to have a significant impact on the increase of food production. This study aims to assess planning design and the implementation of FS-ICM on rice. This study used primary and secondary data included all information related to planning design and the implementation of FS-ICM program at national and regional levels. Data collection was carried out by interviewing the leaders of agricultural institutions associated with activities of FS-ICM and from Focus Group Discussion (FGD) among the group and individual rice farmers at provincial and regency levels in West Java Province in the period of September−October 2014. The data and information were processed descriptively and qualitatively. The results of this study indicated that annual planning of the FS-ICM program was in fact not based on the results of annual evaluation of the implementation and the performance of FS-ICM. During five-year period, annual target of the FS-ICM had been arranged to be increased at a very high rate, regardless of the limited capacity and the unsuccessful implementation of the program. This study had also indicated that planning and implementation of FS-ICM in the field was not fully in accordance with the basic concept of ICM. The rate of adoption of ICM technology components among the rice farmers was quite low, besides the limited number and quality of agriculture extension workers to support this program. It is suggested reporting systems and socialization program improvement, well-functioning LL, encouraging the mobilization of extension, fostering local growers, establishing better coordination between central and local governments as well as implementers in the field, and also building and repairing aspects of processing, marketing and farmers groups. AbstrakSekolah Lapang Pengelolaan Tanaman Terpadu (SL-PTT) merupakan salah satu komponen dalam program Peningkatan Produksi Beras Nasional yang dilaksanakan Kementerian Pertanian pada tahun 2009−2014. Dengan dukungan anggaran yang besar, pelaksanaan SL-PTT diharapkan dapat berdampak nyata pada peningkatan produksi pangan. Kajian ini bertujuan untuk mengkaji perencanaan dari implementasi kegiatan SL-PTT padi sawah. Data yang digunakan dalam kajian ini adalah data primer dan sekunder, meliputi informasi tentang perencanaan dan implementasi SL-PTT di pusat dan daerah. Pengumpulan data dilakukan melalui wawancara dengan pimpinan instansi pertanian yang terkait dengan kegiatan SL-PTT serta focus group discussion (FGD) di antara kelompok tani/petani padi sawah pada tingkat provinsi dan kabupaten di Provinsi Jawa Barat yang dilaksanakan pada bulan September−Oktober 2014.  Pengolahan data dan informasi dilakukan dengan metode deskriptif kualitatif. Hasil kajian menunjukkan bahwa kegiatan perencanaan tahunan SL-PTT tidak didasarkan pada hasil evaluasi pelaksanaan dan kinerja implementasi SL-PTT di lapangan. Selama periode lima tahun, target tahunan SL-PTT terus ditambah dengan tingkat kenaikan yang tinggi, tanpa memperhatikan kemampuan daya dukung keberhasilan program. Kajian ini juga menunjukkan perencanaan dan implementasi SL-PTT di lapangan tidak mengacu sepenuhnya pada konsep dasar PTT, tingkat adopsi komponen teknologi PTT masih rendah, dan jumlah serta kualitas penyuluh pertanian terbatas untuk mendukung keberhasilan program SL-PTT ini. Implikasi kebijakan yang disarankan ialah perbaikan sistem pelaporan dan sosialisasi program, memfungsikan LL secara baik, mendorong mobilisasi penyuluh, menumbuhkan penangkar-penangkar lokal, membangun koordinasi yang baik antara pemerintah pusat, daerah, dan pelaksana di lapangan, serta membangun dan memperbaiki aspek pengolahan, pemasaran, dan kelembagaan kelompok tani.